Erbb2+metastatic breast cancer treatment after progression on trastuzumab: a cost-effectiveness analysis for a developing country (2014)
Objective Breast cancer (BC) and metastatic breast cancer (MBC) are significant causes of deaths amongst women worldwide, including developing countries. The cost of treatment in the latter is even more of an issue than in higher income countries. ErbB2 overexpression is a marker of poor prognosis and the goal for targeted therapy. This study was aimed at evaluating the cost-effectiveness in Colombia of ErbB2+ MBC treatment after progression on trastuzumab.Methods A decision analytic model was constructed for evaluating such treatment in a hypothetical cohort of ErbB2+MBC patients who progressed after a first scheme involving trastuzumab. The alternatives compared were lapatinib+capecitabine (L+C), and trastuzumab+a chemotherapy agent (capecitabine, vinorelbine or a taxane). Markov models were used for calculating progression-free time and the associated costs. Effectiveness estimators for such therapy were identified from primary studies; all direct medical costs based on national fees-guidelines were included. Sensitivity was analyzed and acceptability curves estimated. A 3 % discount rate and third-payer perspective were used within a 5-year horizon.Results L+C dominated its comparators. Its cost-effectiveness ratio was COP $49,725,045 per progression-free year. The factors most influencing the results were the alternatives’ hazard ratios and the cost of trastuzumab.Conclusion Lapatinib was cost-effective compared to its alternatives for treating MBC after progression on trastuzumab using a Colombian decision analytic model.